Study of the optical and structural properties of the (ZnO) membrane, which is prepared by the method of thermal steaming by using the closed oven - Amna Raad Dahham; Sabri Jassim Mohammed; Wlla Mahffod Mohammed (Tikrit Journal of Pure Science)
This study investigated the optical and structural properties of the (ZnO) membrane, which is prepared by the method of thermal steaming in the vacuum by using the closed oven on glass platforms at room temperature. The crystallization of the membranes prepared by X-ray diffraction pattern was diagnosed. The membranes were found to be polymorphic with hexagonal structure and crystal direction (002), the membranes were annealed for (5,15,25) min at (510°C),the results showed the increased height of peaks with their intensity and decreases in the optical gap energy. The study of optical properties also included the recording of both the absorption spectra and the permeability spectrum of the prepared membranes at the wavelength range (250-1100) nm, Also, the rest of the optical constants were calculated as functions of the photon energy, including (absorption coefficient, extinaction cofficient), Where the value of the absorption coefficient for ZnO thin films varies from (1.4 cm-1 to 2.09cm-1), and the value of  extinaction coefficient  varies from (0.6 to 0.38). Transmission spectra showed highly transparent films with band gap energy varies ranging from 3.47ev to 3.3 eV.